The Influence of Copper Powder Morphology on Mechanical Properties of Low-Pressure Cold Sprayed Coatings - D. Grygier; M. Rutkowska-Gorczyca; M.G. Winnicki; T. Wojdat (Archives of Metallurgy and Materials, 2021)
Thermal spraying methods are commonly used to regenerate damaged surface or change materials surface properties. One of the newest methods is cold spraying, where coating is deposited of material in the solid state. Therefore shape and size of the powder particles are very important parameters. The article presents the influence of copper powder morphology on mechanical properties of the coatings (adhesion, hardness, Young’s modulus) deposited with the Low Pressure Cold Spraying method on the AA1350 aluminium alloy substrate. The coatings were deposited using two commercially available copper powders with spherical and dendritic morphology and granulation of –40+10 µm. The bond strength of coatings was determined with the pull off method, the hardness with the Vickers method at load of 2.94 N, while the Young’s modulus through measurement of nanoindentation. Microstructure of the coatings was analysed using the light and scanning electron microscopy (SEM). Shape of the powder influences mechanical properties of the coating significantly. The coatings deposited with dendritic powder had low mechanical properties, hardness of the 81 HV0.3 order and adhesion of about 4 MPa. However changing powder morphology to spherical increased hardness of the coating to 180 HV0.3 and adhesion to 38.5 MPa.